Postsurgical Meningitis Complicated by Severe Refractory Intracranial Hypertension with Limited Treatment Options: The Role of Mild Therapeutic Hypothermia - Popugaev, Konstantin A.; Savin, Ivan A.; Oshorov, Andrew V.; Kurdumova, Natalia V.; Ershova, Olga N.; Lubnin, Andrew U.; Kadashev, Boris A.; Kalinin, Pavel L.; Kutin, Maxim A.; Killeen, Tim; Cesnulis, Evaldas; Melieste, Ronald (Journal of Neurological Surgery Reports, 2014)
Intracranial hypertension is a commonly encountered neurocritical care problem. If first-tier therapy is ineffective, second-tier therapy must be initiated. In many cases, the full arsenal of established treatment options is available. However, situations occasionally arise in which only a narrow range of options is available to neurointensivists. We present a rare clinical scenario in which therapeutic hypothermia was the only available method for controlling intracranial pressure and that demonstrates the efficacy and safety of the Thermogard (Zoll, Chelmsford, Massachusetts, United States) cooling system in creating and maintaining a prolonged hypothermic state. The lifesaving effect of hypothermia was overshadowed by the unfavorable neurologic outcome observed (minimally conscious state on intensive care unit discharge). These results add further evidence to support the role of therapeutic hypothermia in managing intracranial pressure and provide motivation for finding new strategies in combination with hypothermia to improve neurologic outcomes.
Keywords: therapeutic hypothermia; meningitis; intracranial pressure; intracranial hypertension